OPTIMIZATION OF GREEN SYNTHESIS OF GOLD NANOPARTICLES USING CHILI FRUIT EXTRACTS (Capsicum Sp.) - Oktavia, Anggraeni In; Mastuti, Retno; Rosyidah, A’liyatur; Arumingtyas, Estri Laras (LPPM Akafarma Sunan Giri Ponorogo, 2025)
The use of plant extracts as reductants in green synthesis of gold metal nanoparticles (AuNPs) requires optimal conditions of temperature, extract concentration and pH. The objective of this research is to identify the optimal synthesis conditions for producing gold nanoparticles (AuNPs). The reducing agents employed are extracts from three varieties of chili peppers: Katokkon, Cakra Hijau, and Paprika Merah. Variations of plant extract concentrations of 10%, 15%, and 20%, incubation temperatures of 25°C, 37.5°C, and 50°C, and pH levels of 5, 7, and 9. The optimization formula design was determined using Box-Behnken, Design Expert version 13.0. The formation of AuNPs was indicated by a change in the color of the solution from yellow to pink to purple. Surface plasmon resonance was observed in the range of 200-800 nm using a microplate reader. Chili, Katokkon, Cakra Hijau and Red Paprika extracts were able to synthesize Au into AuNPs. The optimal formula for synthesizing AuNPs using Katokkon and Red Paprika extracts at a concentration of 10% while Ckra Hijau at a concentration of 15%. The incubation temperature used was 37.5°C for Katokkon extract and 25°C for Cakra Hijau and Red Pepper extract. The pH level used for the synthesis of AuNPs was pH 5 for all chili pepper extracts.